2023
DOI: 10.3390/biomedicines11030663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin Nanoparticles on Hepatic and Intestinal Enzymes and Stress-Related Genes in Nile Tilapia Fish Exposed to Silver Nanoparticles

Abstract: Recently, nanotechnology has become an important research field involved in the improvement of animals’ productivity, including aquaculture. In this field, silver nanoparticles (AgNPs) have gained interest as antibacterial, antiviral, and antifungal agents. On the other hand, their extensive use in other fields increased natural water pollution causing hazardous effects on aquatic organisms. Quercetin is a natural polyphenolic compound of many plants and vegetables, and it acts as a potent antioxidant and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 125 publications
2
6
0
Order By: Relevance
“…To detect the underlying mechanisms of ZnO-NPs cytotoxicity effect on the zebrafish olfactory organs, the mRNA expression of antioxidant, DNA damage, and apoptosis-related genes was evaluated by qRT-PCR [ 44 ] to support our TEM observations between the control and ZnO-NPs treated groups. It has been observed that ZnO-NPs alter mitochondrial structure and function, resulting in the generation of excessive reactive oxygen species (ROS) that weaken the antioxidant enzyme activity, altogether placing the olfactory cells at oxidative stress risk [ 46 , 47 , 48 , 49 ]. Accordingly, the mRNA expression of antioxidant-related genes, including sod1 , sod2 , gpx1a , gstp1.2 , and cat , was down-regulated in the treated olfactory rosette compared with the control one ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…To detect the underlying mechanisms of ZnO-NPs cytotoxicity effect on the zebrafish olfactory organs, the mRNA expression of antioxidant, DNA damage, and apoptosis-related genes was evaluated by qRT-PCR [ 44 ] to support our TEM observations between the control and ZnO-NPs treated groups. It has been observed that ZnO-NPs alter mitochondrial structure and function, resulting in the generation of excessive reactive oxygen species (ROS) that weaken the antioxidant enzyme activity, altogether placing the olfactory cells at oxidative stress risk [ 46 , 47 , 48 , 49 ]. Accordingly, the mRNA expression of antioxidant-related genes, including sod1 , sod2 , gpx1a , gstp1.2 , and cat , was down-regulated in the treated olfactory rosette compared with the control one ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly [125], revealed that Cd could induce adrenal damage through activation of TLR4/ NF-κB-mediated inflammatory responses which play an essential role in Cd-induced toxic lesions. Moreover [126], elucidated that Cd triggered oxidative damage in the hepatic tissue through a substantial elevation of NF-κB and HSP70 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Silver-NPs toxicity has been shown to up-regulate the expression of hepatic Hsp70, caspase3, and p53 genes in the liver tissue of Nile Tilapia Fish (Farag et al, 2023). Additionally, Silver-NPs have been found to induce an apoptotic response, oxidative stress, and p53 expression in the liver tissue of adult zebrafish (Choi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%